Learn, Change or Perish : A Paradigm Shift about Organisational Structure in the Public Sector Organisation of Bangladesh - Md. Ali, Ahsan; Surena, Sabil; Abang Ekhsan, Abang Othman (ABC Research House, 2018)
Reform is an ongoing process for the organisations to cope with the changing atmosphere. Public sector organisations are ideologically different from its private counterpart, as public sector organisations are more service oriented rather profit orientation. This paper aims to understand the significant structural factors of organisation that has influence on organisational learning in public sector organisation from the context of developing country. This is purely a qualitative study based on inductive approach; it collected the primary data by deploying semi-structured interviews for over a period of more than nine months. This paper reveals several significant factors that have influence on organisational learning in public sector organisation in an emerging country (socio-economic) like Bangladesh by collecting empirical evidence from the study location.